Overview of atrazine biodegradation under different oxidation-reduction conditions (Research, Society and Development, 2021)
The indiscriminate use of the herbicide atrazine in Brazil and in the world has several adverse effects on human health and ecosystems, which can be found in soil, groundwater, in the air and also in living beings, which justifies research focused on biodegradation, impacts and characteristics of this compound. Our work, through a literature review, shows that atrazine's biodegradation can occur through different oxidation reduction conditions, with the participation of aerobic and anaerobic microbial consortia, generating different degradation metabolite intermediates, such as hydroxyatrazine, N -isopropylammilide, cyanuric acid, biuret, allophanate and urea. In addition, we show microorganisms that have already been detected with the potential for degradation of this compound using atrazine as a source of carbon and / or nitrogen, and its metabolic intermediates formed during aerobic and anaerobic degradation processes, as well as the main genes responsible for synthesis of enzymes involved in the degradation of this compound.